Long Time Coming, Long time Gone: the Past, Present and Future of Social History - Gallant, Thomas (Historein, 2013)
This article traces the past, present and future of social history since the field’s emergence in the mid-1960s until the present. It examines the origin and developmental trajectory of the field, analyzing the various challenges it has faced and how it has responded to them. It ends by suggesting one possiblway forward for the field in the 21st century.